Controversies surrounding “Would AI determine the human existence in the future?”–From the perspective of Science Fictions - Zhang, Lizhong; Pei, Jingyi (International Journal of Advanced AI Applications, 2025)
Since the 20th century, Artificial Intelligence (AI) has been a prominent theme in Science Fiction (SF). Works like Frank Herbert’s Dune and Arthur C. Clarke’s 2001: A Space Odyssey portray AI as dystopian entities capable of autonomous harm to humans. In contrast, Isaac Asimov’s Galactic Empire and I, Robot present AI as benevolent allies, aiding humanity in exploration, development, and rescue. These contrasting perspectives form the foundation for envisioning future human-AI interactions. This paper explores these divergent views, examines their real-world implications, and investigates how modern AI advancements are shaping new trends in SF storytelling.